“Trying to Function in the Unfunctionable”: Mothers and COVID-19 - O'Reilly, Andrea (Journal of the Motherhood Initiative for Research and Community Involvement, 2020)
The central directive of the COVID-19 pandemic has been conveyed in two words: stay home. Yet there has been little media coverage, public policy, or social research on how families are managing under social isolation. Few have acknowledged, let alone sought to support, the crucial work mothers are doing as frontline workers to keep families functioning in these times of increasing uncertainty. Mothers do the bulk of domestic labour and childcare, and with social isolation, the burden of care work has increased exponentially, as mothers are running households with little or no support and under close to impossible conditions. Many mothers are also now engaged in paid labour from home and are responsible for their children’s education as schools remain closed indefinitely. Mothers have little to no respite from their 24/7 schedule, since most outdoor activities have been cancelled for children, and no one is allowed into their homes. Add income or employment loss, financial or housing instability, food insecurity, single parenting, abusive situations, or recent experiences of migration and the stress is amplified. The article explores the care and crisis of mothers under COVID-19 through an examination of comments and discussions on the Facebook group Mothers and COVID-19, which I set up over a two-week period in early May 2020. The article considers how mothers are managing the new requirements of motherwork under the destabilizing restraints of this pandemic. It also addresses and asks why the essential and frontline work of mothering in this pandemic has been so discounted, disregarded, and dismissed by governments, media, and the larger society. The article seeks to make visible what has been made invisible and render audible what has been silenced—the labour of motherwork under COVID-19—in order to inform, support, and empower mothers through and after this pandemic.